2007
DOI: 10.1002/art.22985
|View full text |Cite
|
Sign up to set email alerts
|

High‐sensitivity C‐reactive protein in chronic low back pain with vertebral end‐plate modic signal changes

Abstract: Objective. To assess high-sensitivity C-reactive protein (hsCRP) level as a measure of low-grade inflammation in relation to Modic vertebral end-plate marrow signal change on magnetic resonance imaging (MRI) in patients with chronic low back pain. Methods. All patients hospitalized for chronic low back pain in our institution were prospectively enrolled in this pilot study. Serum hsCRP concentration was measured by immunoturbidimetric assay. MR images were evaluated independently by a panel of 2 spine speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 21 publications
(37 reference statements)
11
66
1
5
Order By: Relevance
“…These results are in agreement with the study by Maigne and Balard, [19], who reported a positive response to a short course of oral steroids in patients with LBP and the presence of pain at night, worse pain on waking up and pain with lumbar extension. Our results also agree with Rannou et al [8], who in a pilot study reported an association of the worst painful moment during late night and morning and Modic 1 changes and a possible association of longer duration of morning stiffness. Presence of inflammatory characteristics of pain must be linked with radiological and biological findings suggesting an inflammatory mechanism [6].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…These results are in agreement with the study by Maigne and Balard, [19], who reported a positive response to a short course of oral steroids in patients with LBP and the presence of pain at night, worse pain on waking up and pain with lumbar extension. Our results also agree with Rannou et al [8], who in a pilot study reported an association of the worst painful moment during late night and morning and Modic 1 changes and a possible association of longer duration of morning stiffness. Presence of inflammatory characteristics of pain must be linked with radiological and biological findings suggesting an inflammatory mechanism [6].…”
Section: Discussionsupporting
confidence: 94%
“…Biopsies of the Modic 1 vertebral body show replacement of marrow by richly vascularized fibrous tissue [2] and elevated number of tumor necrosis factorimmunoreactive cells in the intervertebral disc [7]. In addition, increased levels of high-sensitivity C-reactive protein were reported in patients with chronic LBP and Modic 1 changes by Rannou et al [8]. In this study, patients with Modic 1 changes seem to have a longer duration of morning stiffness and worst painful moment at night and morning.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous studies have indicated elevated inflammatory mediators are found in herniated lumbar discs [78] and vertebral end-plate changes [79]. Only one study though has examined the interrelations among obesity, systemic inflammation, and LBP.…”
Section: Obesity Systemic Inflammation and Low Back Painmentioning
confidence: 99%
“…These authors noticed that infl ammatory cytokines and nerve ingrowth into vertebral endplates may be a cause of discogenic LBP and that type I changes, representing more active infl ammation, seem to be mediated by proinfl ammatory cytokines, whereas type II and III changes could be more quiescent stages of the process. Rannou et al 21 reported that low-grade infl ammation indicated by high serum high-sensitivity C-reactive protein (hsCRP) level in patients with chronic LBP could point to MCI signal changes. However, Briggs et al 22 noticed that no differences hsCRP level between MCI and MCII due to the low sample size of MCI cases.…”
Section: Discussionmentioning
confidence: 99%